Radiosurgery-Based AVM Scale Is Proposed for Combined Embolization and Gamma Knife Surgery for Brain Arteriovenous Malformations - Meng, Xiangyu; He, Hongwei; Liu, Peng; Gao, Dezhi; Chen, Yu; Sun, Shibin; Liu, Ali; Li, Youxiang; Jin, Hengwei (Frontiers in Neurology, 2021)
Background and purpose: To evaluate whether radiosurgery-based AVM scale (RBAS) could be used to predict obliteration of brain arteriovenous malformations (bAVMs) supposed for combined endovascular embolization (EMB) and gamma knife surgery (GKS) treatment. Methods: BAVM patients underwent GKS with or without previous embolization from January 2011 to December 2016 at our institution were retrospectively reviewed. Patients were categorized into combined treatment group and GKS group. A 1:1 Propensity Score Matching (PSM) was used to match two groups. Pre-embolization and pre-GKS RBAS were assessed for every patient. Multivariate analysis was performed to find factors associated with complete obliteration in combined treatment group. Survival analysis based on sub-groups according to RBAS was performed to compare obliteration rate and find cut-offs for appropriate treatment modalities. Results: A total of 96 patients were involved and each group comprised 48 patients. There was no difference between two groups in terms of obliteration rate (75.0% VS 83.3%, p=0.174). Pre-EMB RBAS(p=0.010) and number of feeding arteries(p=0.014) were independent factors associated with obliteration rate in combined treatment group. For combined treatment patients, sub-group analysis according to pre-EMB RBAS (score<1.0, 1.0-1.5 and >1.5) showed statistical difference in obliteration rate(p=0.002). Sub-group analysis according to RBAS between two groups showed that the obliteration rate of GKS group is significantly higher than combined group when RBAS>1.5 (47.4% VS 66.7%, p=0.036). Conclusions: RBAS is proposed to be efficient in predicting obliteration of bAVMs supposed to receive combined EMB and GKS treatment. Patients with RBAS＞1.5 is inclined to be more suitable for GKS instead of combined treatment.